The current international political environment and the war on Syria - ميليش فريد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The major transformations that occurred in the international environment in the post-Cold War era and the events of September 2001, and the contemporary interest in the regional bloc or what is called “New Regionalism” which constitutes one of the important trends in contemporary international relations, cast their shadows on the regional environment and the theater of American military operations, starting with the war on Afghanistan, then the occupation of Iraq, and then targeting Syria as a result of the current international political environment, and the stages that the war on Syria went through, based on the importance of Syria in all fields and the political and economic ambitions to dominate the region.